Non-invasive monitoring of transplanted endothelial progenitor cells in diabetic ischemic stroke models. (February 2015) - Bai, Ying-Ying; Wang, Lishan; Peng, Xin-Gui; Wang, Yuan-Cheng; Chang, Di; Zheng, Shuyan; Ding, Jie; Li, Cong; Ju, Shenghong
Abstract: Endogenous endothelial progenitor cells (EPCs) are functionally impaired in hyperglycemia through the p38 MAPK signaling pathway. However, the number and function of transplanted exogenous EPCs in diabetic animals remains unclear. The objectives of this study were to establish a non-invasive imaging strategy to monitor the homing of transplanted EPCs in diabetic stroke mice and to assess the effect of RWJ 67657, an inhibitor of p38 MAPK, on the homing ability of exogenous EPCs. Bone marrow-derived EPCs were labeled in vitro with a multi-functional nanoprobe modified with paramagnetic chelators and fluorophores before being infused into stroke mice. The signal of the nanoprobe reached its peak on day 5 in both magnetic resonance imaging and near-infrared fluorescence imaging after EPC transplantation in wild-type stroke models. The signal enhancement of diabetic stroke models was significantly lower than that of wild-type controls. However, the signal intensity of diabetic stroke models significantly increased after oral administration of RWJ 67657, indicating that more transplanted EPCs migrated to the ischemic brain. Furthermore, the increased exogenous EPCs induced remarkably greater angiogenesis after stroke. These results suggest that this dual-modal imaging strategy is feasible for non-invasively monitoring transplanted cells in vivo .